Biodiesel production with DES (deep eutectic solvent) catalyst using used cooking oil feedstock through two-stage transesterification process - Fitri Hadiah; Nur Kemala Debi Lestari; Mughni Ayahanda Putri; Budi Santoso; Rahmawati Rahmawati (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Most of biodiesel in Indonesia is still produced by costly processed utilizing pricey catalysts and high grade fatty acid methyl esther (FAME). Low cost catalysts need to be invented in order to make biodiesel more affordable, while raw material also need to be obtained from low cost alternatives. such as broadly available waste cooking oil.This research used waste cooking oil as raw material in biodiesel transesterification process, utilizing DES (Deep Eutectic Solvent) K2CO3-gliserol, as alternative catalyst. The output was biodiesel with near SNI 7182:2015 criteria. Optimum biodiesel production was achieved in low 65 oC temperature while utilizing two step transesterification process using DES K2CO3-gliserol 5.5 % and 35 % methanol, whereas glycerol total was 0.32 % and methyl esther contain was 96.89 %.